DEVELOPING INTERACTIVE LEARNING MEDIA OF â€œVENN GRAMâ€ TO IMPROVE CONCEPTUAL UNDERSTANDING OF SET OPERATIONS - Prillyana, Fadhanila Syainuralita; Cahyono, Hendarto; Jamil, Anis Farida (Study Program of Mathematics Education University of Muhammadiyah Malang, 2020)
This research aimed at discovering the validity and effectiveness of the interactive media of